RETHINKING HUMANITY’S PROGRESS IN LIGHT OF COVID-19 - Keenan, James F. (Asian Horizons, 2020)
This article explores the present circumstances where we find ourselves astonished by our own inability to deal with the crisis more collectively and supportively. Through research data that highlights how inequity is driving the worst of this virus and then the oversight of major social commentators, we examine the present precarity of humanity, the need for greater solidarity and vulnerability, the danger of misinformation and scapegoating, and the call for the church to rearticulate its mission today. The article concludes reflecting on the evident confusion and distrust around the world and suggests that the way forward is to acknowledge our guilt for the inequities, our need for epistemic humility, and our pledge to recognize and accompany those most at risk.